Microgravity × Radiation: A Space Mechanobiology Approach Toward Cardiovascular Function and Disease - Basirun, Carin; Ferlazzo, Melanie L.; Howell, Nicholas R.; Liu, Guo-Jun; Middleton, Ryan J.; Martinac, Boris; Narayanan, S. Anand; Poole, Kate; Gentile, Carmine; Chou, Joshua (Frontiers in Cell and Developmental Biology, 2021)
In recent years, there has been an increasing interest in space exploration, supported by the accelerated technological advancements in the field. This has led to a new potential environment that humans could be exposed to in the very near future, and therefore an increasing request to evaluate the impact this may have on our body, including health risks associated with this endeavor. A critical component in regulating the human pathophysiology is represented by the cardiovascular system, which may be heavily affected in these extreme environments of microgravity and radiation. This mini review aims to identify the impact of microgravity and radiation on the cardiovascular system. Being able to understand the effect that comes with deep space explorations, including that of microgravity and space radiation, may also allow us to get a deeper understanding of the heart and ultimately our own basic physiological processes. This information may unlock new factors to consider with space exploration whilst simultaneously increasing our knowledge of the cardiovascular system and potentially associated diseases.